No Evidence for Erythro-Myeloid Progenitor-Derived Vascular Endothelial Cells in Multiple Organs. Issue 10 (23rd October 2020) - Feng, Teng; Gao, Zibei; Kou, Shan; Huang, Xinyan; Jiang, Zhen; Lu, Zhengkai; Meng, Jufeng; Lin, Chao-Po; Zhang, Hui
Abstract : Rationale: Endothelial cells are thought to emerge de novo from the mesoderm to form the entire circulatory system. Recently, erythro-myeloid progenitors (EMPs) have been proposed to be another remarkable developmental origin for blood vessels in multiple organs, including the hindbrain, liver, lung, and heart, as demonstrated by lineage tracing studies using different genetic tools. These observations challenge the current consensus that intraembryonic vessels are thought to expand solely by the proliferation of preexisting endothelial cells. Resolution of this controversy over the developmental origin of endothelial cells is crucial for developing future therapeutics for vessel-dependent organ repair and regeneration. Objective: To examine the contribution of EMPs to intraembryonic endothelial cells. Methods and Results: We first used a transgenic mouse expressing a tamoxifen-inducible Mer-iCre fusion protein driven by the Csf1r (colony stimulating factor 1 receptor) promoter. Genetic lineage tracing based on Csf1r-Mer-iCre-Mer showed no contribution of EMPs to brain endothelial cells identified by several markers. We also generated a knock-in mouse line by inserting an internal ribosome entry site-iCre cassette into the 3′ untranslated region of Csf1r gene to further investigate the cellular fates of EMPs. Similarly, we did not find any Csf1r-ires-iCre traced endothelial cells in brain, liver, lung, or heart in development either. Additionally, we found that Kit (KIT proto-oncogene receptor tyrosine kinase) was expressed not only in EMPs but also in embryonic hindbrain endothelial cells. Therefore, Kit promoter–driven recombinase, such as Kit-CreER, is a flawed tool for lineage tracing when examining the contribution of EMPs to hindbrain endothelial cells. We also traced CD45 (protein tyrosine phosphatase receptor type C; Ptprc) + circulating EMPs and did not find any CD45 lineage-derived endothelial cells during development. Conclusions: Our study suggested that EMPs are not the origin of intraembryonic endothelial cells. Abstract : Supplemental Digital Content is available in the text.